(untitled) (Bangladesh Journal of Animal Science, 2012)
The present study was conducted to investigate the milk quality from different genotype. A total 48 dairy cows belong to different genotypes such as Holstein cross, Jersey cross, Sahiwal cross and Red Chittagong were selected. Milk compositional viz. specific gravity, Acidity test, Fat test, Protein test, Solids-not-fat (SNF) test and total solids (TS) test were carried out. It was observed that the higher specific gravity of milk was obtained from Jersey cross and Red Chittagong genotype, which was significantly higher (P<0.01) than the other genotype of dairy cows. The highest acidity (%) was observed (0.165±0.014) in Red Chittagong and the lowest acidity (0.118±0.025) in Sahiwal cross. The highest fat (%) was observed from Red Chittagong cows milk which was statistically higher from Jersey cross and Sahiwal cross and the lowest fat (%) was found in the milk of Holstein cross cows. The highest SNF value was obtained from Jersey cross and the lowest from Sahiwal cross. On the other hand, Holstein cross and Red Chittagong was nearly similar. Red Chittagong milk sample showed the highest TS value and the lowest value was observed from Holstein cross. The highest protein value was found from Red Chittagong and the lowest from Holstein cross but the protein content of other two genotypes were nearly similar. DOI: http://dx.doi.org/10.3329/bjas.v37i1.9868 BJAS 2008; 37(1): 53-56